PYEZO RESISTANCE OF DEFORMATED SILICON P – TYPE - Orazgulyev, B.; Bigozha, O. (Recent Contributions to Physics, 2009)
The experimental result gat by silicon p - type is led in this article by studying longitudinal and transverse pyezo resistance. It s shown that immonotonous character of transverse resistance is determined by comparative contribution to pyezo resistance mechanism migration of current carrier from the zone of «light» holes into «heavy» holes and the mechanism connected with discreasing meaning of effective mass of holes in the zone of heavy holes in conseguence of reconstruction of power spectrum with monoaxes deformation taking off degenerasy of valency zone.
Keywords: pyezo resistance